PHILOSOPHY AND ANARCHIST CRITIQUE - Vaccaro, Salvo (Soft Power, 2025)
It is easy to think of anarchism as a political theory in the modern “storm” brought about by the rational enlightenment versus the darkness of religious dogmas and the political theology that inspired theory and practice of absolute sovereignty first, and constitutional sovereignty afterwards. It may also be conceived as an extreme form of the politically charged theories of the Enlightenment, as opposed to other contemporary political theories such as liberalism and utopic socialism first, or Marxist socialism at a later stage. As such, over two centuries later, it is subject to the wear of time, to the post-modern nullification with which some seek to liquidate the certainties of a blind, all-powerful reason already denounced, in its defining aporia, by Adorno and Horkheimer.